The development of highly dense highly protected surfactant ionizable lipid RNA loaded nanoparticles - González-Rioja, Ramon; Salazar, Vivian A.; Bastús, Neus G.; Puntes, Victor (Frontiers in Immunology, 2023)
The long quest for efficient drug administration has been looking for a universal carrier that can precisely transport traditional drugs , new genomic and proteic therapeutic agents. Today, researchers have found conditions to overcome the two main drug delivery dilemmas. On the one side, the versatility of the vehicle to efficiently load, protect and transport the drug and then release it at the target place. On the other hand, the questions related to the degree of PEGylation which are needed to avoid nanoparticle (NP) aggregation and opsonization while preventing cellular uptake. The development of lipid particles has yielded with the improvement of ionizable lipid nanoparticles (iLNPs), which are able to overcome most of the typical drug delivery problems and have succeeded at being approved and massively used in the late SARS-CoV-2 as a prophylactic vaccine. These ILNPs are built by electrostatic aggregation of surfactants, the therapeutic agent, and lipids that self-segregate from an aqueous solution, forming nanoparticles stabilized with lipid polymers, such as PEG. These vehicles overcome previous limitations such as low loading and high toxicity, likely thanks to low charge at the working pH and reduced size, and their entry into the cells via endocytosis rather than membrane perforation of fusion, always associated with higher toxicity. We herein revise their primary features, synthetic methods to prepare and characterize them, pharmacokinetic (administration, distribution, metabolization and excretion) aspects, and biodistribution and fate. Owing to their advantages, iLNPs are potential drug delivery systems to improve the management of various diseases and widely available for clinical use.